Rudyard Kipling's Just so stories and their Czech translation - Kasíková, Petra (Univerzita Pardubice, 2012)
The aim of this bachelor paper is to compare two Czech translations of Rudyard Kipling's Just So Stories. The first translation was published in 1958 by Zdeněk Hobzík and the second one provided by Jaroslav Vančura is from the year 1978. In the theoretical part of this paper, work of Rudyard Kipling is examined, followed by defining children's litrature, and finally a process of translation is explained. The practical part consists of comparing two Czech translations of Just So Stories. Specific examples are provided for this analysis. In the final part, results of the analysis are presented.
Just so stories od Rudyarda Kiplinga a jejich české překlady
Keywords: Kipling, Rudyard; Povídky jen tak; Bajky nebajky; překlad; analýza; Just So Stories; translation; analysis